Sustainability Analisys and The Effect Of Honeybee-Coffee Plantation Integration Model On Improving - Saepudin, Rustama (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2014)
Â The objective of this study was to evaluate the sustainability and the improvement of Apis cerana honey production which was placed at Coffee Plantation. The experiment was arranged in a Completely Randomized Design with two treatments and ten replications. The result of this study was the sustainability index was increase to 76.00 (very good) from 59.50 (good). The other result was the honey production of Apis cerana at coffee plantation was significantly higher by 114% than that outside the plantation and the caffee been productivity was inproved as muach as 10.55%. The integration of honey bee and coffee plantation was able to inprove the farmer general income and change their mind that vegetation (trees) must be saved due to the source of honey bee feed (nectar and pollen). As a conclusion that integrated honeybee and coffee plantation effected on improving of sustainability as well as Apis cerana and coffee bean productivity Key words:Â Honey, coffee, integration, sustainability, index